Legal and Ethical Aspects of ‘Best Interests’ Decision-Making for Medical Treatment of Companion Animals in the UK - Carol Gray; Peter Fordyce (Animals, 2020)
Medical decisions for young children are made by those with parental responsibility, with legal involvement only if the decision is potentially detrimental to the child’s welfare. While legally classified as property, some argue that animals are in a similar position to children; treatment decisions are made by their owners, posing a legal challenge only if the proposed treatment has the potential to cause harm or unnecessary suffering, as defined by animal protection legislation. This paper formulates the approach to a ‘best interests’ calculation, utilising the factors included in the United Nations Convention on the Rights of the Child and relying on exchange of information between the human parties involved. Although this form of decision-making must primarily protect the animal from unnecessary suffering, it recognises that the information provided by the owner is critical in articulating the animal’s non-medical interests, and hence in formulating what is in the animal’s best overall welfare interests. While statute law does not mandate consideration of ‘best interests’ for animals, this approach might reasonably be expected as a professional imperative for veterinary surgeons. Importantly, this version of a ‘best interests’ calculation can be incorporated into existing ethical frameworks for medical decision-making and the humane treatment of animals.